Sobrevida en adultos coinfectados con el Virus de la Inmunodeficiencia Humana y Tuberculosis en Loreto 2017 – 2024 - Flores Seminario, Ana Betty Carolina (2025)
Objectives: To determine survival in adults over 17 years of age co-infected with HIV/TB in the Loreto region, as well as to identify the associated sociodemographic and clinical factors and estimate the prevalence of tuberculosis resistant to anti-tuberculosis drugs. Methods: A retrospective cohort study was conducted that included 1,020 individuals registered in the Tuberculosis Management Information System between 2017 and 2024. Results: The median age at diagnosis of coinfection was 34 years (IQR: 25 75), and 81.6% were male. The prevalence of resistance to anti-tuberculosis drugs was 8.0%. The mean survival time was 66.15 months (95% CI: 63.47 68.84) after diagnosis of co-infection. Cumulative survival at one and two years was 72% and 70%, respectively, with a mortality rate of 11.39 deaths per 100 person-years of follow-up. Patients who successfully completed anti tuberculosis treatment had a mean survival of 89.3 months compared to 37.3 months and a median of 5 months in those who did not (p = 0.001). Therapeutic success was associated with a 94.3% reduction in the risk of death (HR = 0.057; 95% CI: 0.038–0.084; p < 0.001), while being young, between 18 and 29 years of age, reduced the risk by 51.4% (HR = 0.486; 95% CI: 0.274–0.863; p = 0.014). Conclusions: The success of tuberculosis treatment and adherence to ART are key factors. It is recommended that HIV/TB coinfection be addressed jointly, strengthening early detection, therapeutic adherence, and clinical follow-up to reduce mortality.